The Influence of Brand Trust, Brand Affect, Service Quality on Purchase Decisions at Rooster Coffee Sidoarjo: Pengaruh Brand Trust, Brand Affect, Service Quality Terhadap Keputusan Pembelian pada Rooster Coffee Sidoarjo - Julianto, Rachmat; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of Brand Trust, Brand Affect and Service Quality on Purchase Decisions at Rooster Coffee Sidoarjo. This research is a descriptive study using quantitative methods. data retrieval technique is by distributing questionnaires to consumers who have visited Rooster Coffee as many as 100 respondents. The analysis technique used in this study is multiple linear regression using SPSS version 22 for windows. The results of this study indicate that the Brand Trust variable affects purchasing decisions, the Brand Affect variable affects purchasing decisions and the Service Quality variable affects purchasing decisions on Rooster. Coffee Sidoarjo.